Metoda Sił dla Układów Lepkosprężystych - Kubik, J. (Engineering Transactions, 1970)
In the paper the equation is given of the method of forces for visco-elastic systems, and the properties of the given set of equations are analyzed. In particular, a class of load functions has been separated ensuring the identity of the states of stress in the systems: elastic and analogous visco-elastic (Theorem 1 and 2). Furthermore, the case is analyzed of states of stresses caused by the action of a periodical load (Theorem 3).